Стратегічне планування діяльності підприємств молокопереробної галузі Ураїни та напрями їх стратегічного розвитку - Ольхова, Анастасія Андріївна (НТУ "ХПІ", 2017)
У статті проаналізовано сучасний стан і тенденції розвитку молокопереробної галузі в Україні, а також виявлені особливості діяльності українських молокопереробних підприємств. Запропоновано рекомендації щодо використання стратегічного планування з метою забезпечення виживання та довгострокового розвитку молокопереробних підприємств, та визначені можливі шляхи стратегічного розвитку підприємств галузі.

The article analyzes the current state, the development trends of the milk processing industry in Ukraine and identifies the main features of the industry development. The strategic planning of the activity of dairy enterprises is of particular importance in modern conditions, because enterprises in the industry need to withst and the influence of a large number of adverse factors as well as seek new ways of survival and development. The possibilities of improving the activity of milk processing enterprises through the introduction of strategic planning at enterprises have been analyzed. Recommendations on the use of st rategic planning for the purpose of ensuring the survival and long-term development of milk processing enterprises are suggested, and possible ways of strategic revitalization of enterprises of the industry are identified.
Strategic planning of the enterprises of milk processing industry of Ukraine and directions of their strategic development
Keywords: молокопереробне підприємство; конкурентні переваги; обсяг переробки; сире молоко; дефіцит; strategic planning; strategic development; milk processing industry; milk processing enterprise; competitive advantages